1997
DOI: 10.1016/s0014-5793(97)01051-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Cu,Zn superoxide dismutase typical of familial amyotrophic lateral sclerosis induces mitochondrial alteration and increase of cytosolic Ca2+ concentration in transfected neuroblastoma SH‐SY5Y cells

Abstract: We have set up a model system for familial amyotrophic lateral sclerosis (FALS) by transfecting human neuroblastoma cell line SH-SY5Y with plasmids directing constitutive expression of either wild-type human Cu,Zn superoxide dismutase (Cu,ZnSOD) or a mutant of this enzyme (G93A) associated with FALS. We have tested mitochondrial function and determined cytosolic Ca 2+ concentration in control cells (untransfected) and in cells expressing either wild-type Cu,ZnSOD or G93A. We report that G93A induces a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(29 citation statements)
references
References 29 publications
(22 reference statements)
1
26
0
Order By: Relevance
“…No significant differences were seen for complex I and III activity. Defects in the mitochondrial membrane potential in G93A SOD1 transfected SH-SY5Y cells have also been observed [50]. However, another study found the activities of mitochondrial ATP synthesis, cytochrome c oxidase, and citrate synthase were unchanged in cells expressing G93A or G85R mutant SOD1 in comparison to control cells [51], indicating not only the variability in using different cell models to study disease but also the complex multi-factorial nature of the disease and how multiple factors are likely to influence functional capacity.…”
Section: Discussionmentioning
confidence: 91%
“…No significant differences were seen for complex I and III activity. Defects in the mitochondrial membrane potential in G93A SOD1 transfected SH-SY5Y cells have also been observed [50]. However, another study found the activities of mitochondrial ATP synthesis, cytochrome c oxidase, and citrate synthase were unchanged in cells expressing G93A or G85R mutant SOD1 in comparison to control cells [51], indicating not only the variability in using different cell models to study disease but also the complex multi-factorial nature of the disease and how multiple factors are likely to influence functional capacity.…”
Section: Discussionmentioning
confidence: 91%
“…SH-SY5Y human neuroblastoma cell line transfected with either WT or G93A mutant linked with fALS were routinely cultured in growth medium and were used as a valid and robust in vitro system to investigate the cellular excitotoxicity and mitochondria mediated alterations associated with SOD1-G93A mutations (Carri et al, 1997; Goos et al, 2007; Jaiswal et al, 2009). Detail descriptions about the transfection strategy, cell culture maintenance, cell culture growth medium and procedures are described earlier (Jaiswal et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Mutant forms of SOD1 alter redox balance (decrease GSH, increase GSSG), reduce mitochondrial ETC function (complexes I, II+III, and IV) and subsequently reduce ATP levels in the NSC34 motor neuron cell line [262]. SH-SY5Y cells transfected with G93A mutant SOD1 display loss of mitochondrial membrane potential, and increased cytosolic calcium concentrations [261]. In Neuro2A cells, localization of mutant SOD1 (both G93A and G85R) to mitochondria was associated with the release of cytochrome c and caspase-dependent apoptosis [266].…”
Section: Mitochondrial Medicine and Alzheimer’s Diseasementioning
confidence: 99%